TANGGUNG JAWAB ETIKA ADVOKAT DALAM MENYEDIAKAN JASA HUKUM UNUTK MASYARAKAT MISKIN (PRO-BONO) - Lubis, Fauziah; Haikal, Mhd; Hafidz, Maulana Abdul; Munthe, Fikri Ramadhan; Azzahra, Nurfatimah; Hasibuan, Putri Dahlia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Advokat is a profession that provides legal services both in court and outside of cort that meets the requirements based on the provisions of the Advokat Law. And Advocates have a professional code of ethics, one of which is providing free legal assistance to poor people. However, we often see information on social media that poor people rarely get justice which is caused by various things and one of them is because they cannot hire/hire an Advocate. Because of this, the author wonders how an Advocate is responsible for the code and standars of his profession. This research aims to comprehensicely examine the responsibilities of Advocates regarding their professional code of ethics in providing legal service to poor communities. This research uses the method, systematic literature review (SLR) with the aim of drawing conclusions from pouchtian’s findings which investigate the professional ethics of Advocates in providing legal services free of charge to poor people. The results of the literature review (SLR) study conducted on land concluded that legal services for the poor provided by team Advocates were less effective due to the fact that